Engineered ipilimumab variants that bind human and mouse CTLA-4 - Brett Robison; SJ Diong; Anusha Kumar; Thomas M. Moon; Olin Chang; Bryant Chau; Christine Bee; Ishita Barman; Arvind Rajpal; Alan J. Korman; Sean West; Pavel Strop; et al. (mAbs)
Testing of candidate monoclonal antibody therapeutics in preclinical models is an essential step in drug development. Identification of antibody therapeutic candidates that bind their human targets and cross-react to mouse orthologs is often challenging, especially for targets with low sequence homology. In such cases, surrogate antibodies that bind mouse orthologs must be used. The antibody 9D9, which binds mouse CTLA-4, is a commonly used surrogate for CTLA-4 checkpoint blockade studies in mouse cancer models. In this work, we reveal that 9D9 has significant biophysical dissimilarities to therapeutic CTLA-4 antibodies. The 9D9-mCTLA4 complex crystal structure was determined and shows that the surrogate antibody binds an epitope distinct from ipilimumab and tremelimumab. In addition, while ipilimumab has pH-independent binding to hCTLA-4, 9D9 loses binding to mCTLA-4 at physiologically relevant acidic pH ranges. We used phage and yeast display to engineer ipilimumab to bind mouse CTLA-4 with single-digit nM affinity from an initial state with no apparent binding. The engineered variants showed pH-independent and cross-reactive binding to both mouse and human CTLA-4. Crystal structures of a variant in complex with both mouse and human CTLA-4 confirmed that it targets an equivalent epitope as ipilimumab. These cross-reactive ipilimumab variants may facilitate improved translatability and future mechanism-of-action studies for anti-CTLA-4 targeting in murine models.